ASSESSING THE HYDROCHEMICAL CHARACTERISTICS OF THE ORGANIC SHRIMP MODEL AT TAM GIANG COMMUNE, NAM CAN DISTRICT, CA MAU PROVINCE - Tho, Nguyen; Khanh, Dang Nguyen Nha (Vietnam Journal of Marine Science and Technology, 2018)
This paper clarifies the hydrochemical characteristics of the organic shrimp model certified by Naturland at Tam Giang commune, Nam Can district, Ca Mau province. Pond water was sampled in 8 ponds at 3 points of time of distinct precipitation fluctuations during the year (March, July and November 2015) and hydrochemical parameters related to shrimp were analysed. Results show that salinity, total alkalinity and total hardness are largely dependent on the seasonal precipitation and evapotranspiration, highest in the middle of the dry season (March) and gradually reduced until the wet season-dry season transition (November). Most of the parameters fluctuate within the sampling times but still remain suitable for shrimp. The major constraints include oxygen supersaturation during daylight hours (7.48 ± 0.45 mg/l), low concentrations of soluble nutrients (NH4-N 0.21 ± 0.05 mg/l, NO3-N 0.06 ± 0.02 mg/l, PO4-P 0.02 ± 0.01 mg/l), and high iron contents (Fe2+ 0.08 ± 0.01 mg/l, Fe3+ 0.64 ± 0.14 mg/l) as compared to limits for shrimp aquaculture. The total shrimp yields are very low (355.4 kg/ha water surface/year in which wild shrimp species have accounted for 55%), positively correlated with water depth and temperature but negatively correlated with Fe2+. To improve pond water quality and shrimp yield, it is recommended to increase water depth, nutrient concentrations and restrict the effects of runoff at the beginning of the wet season.